Polityka informacyjna w zakresie gospodarowania odpadami medycznymi szpitali województwa zachodniopomorskiego (Research Bulletins of the Faculty of Economic Sciences, 2018)
The aim of this paper is to determine whether hospitals in Zachodniopomorskie Voivodeship, operating in the network of hospitals, have a developed policy for the management of medical waste and whether such a policy is placed on their websites. The authors of the study have analyzed the literature of the subject, legal acts and the results of the Supreme Chamber of Control’s audit concerning the management of medical waste. This enabled to formulate the following research thesis – “hospitals operating in the network of hospitals, which receive public funds for medical activity, should develop and implement a policy for the management of medical waste. Such a policy should be publicly disclosed, for example, on the websites of hospitals”. The analysis of the examined hospitals’ websites enabled to determine whether the tested hospitals publish information about the management of medical waste and how detailed the published information is.
Keywords: hospitals, medical waste, information policy, network of hospitals, websites